Neuroscience-based Learning Model in Early Childhood Education - Novita Ashari; Tien Asmara Palintan; Putri Annisa (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
Preschool teachers expect to enhance students' intellectual abilities by implementing brain-based learning stimulation in children. However, numerous preschool teachers remain uninformed about the brain's functioning in children. This study aims to establish a neuroscience-based learning model inside early childhood education institution. The study is applied to the 4D development paradigm, which comprises four stages: defining, designing, developing, and disseminating. The study involved 30 kindergarten/RA instructors in Parepare City, selected by purposive sampling, ensuring that the participants had not previously received training related to neuroscience. The data collection procedures employed included observation, interviews, needs analysis, questionnaires, and both pretests and posttests. Qualitative data analysis techniques are descriptive methodologies, whereas quantitative data analysis encompasses expert validation, teacher response surveys, and effectiveness assessments. This project develops a neuroscience-based learning model presented in a guide package as a validated teaching module. After providing content derived from the developed modules, the results indicated an enhancement in participants' scores. The neuroscience learning approach effectively enhances the knowledge of Islamic kindergarten educators. The findings of this study can serve as suggestions for educators and policymakers to improve and elevate the quality of learning in early childhood education.